Electron flux and microbial community in microbial fuel cells (open-circuit and closed-circuit modes) and fermentation. (1st July 2015) - Yu, Jaecheul; Park, Youghyun; Lee, Taeho
Abstract: A closed-circuit microbial fuel cell (C-MFC) was operated to investigate the electron flux under fed-batch mode, and the results were compared to those of open-circuit MFC (O-MFC) and a fermentation reactor (F-reactor). The current was the largest electron sink (52.7 % of influent SCOD) in C-MFC, whereas biomass and methane gas were the most significant electron sinks in O-MFC and F-reactor. Interestingly, some of the unknown sink may have accumulated in the electrode of O-MFC. Principal component analysis based on gradient gel electrophoresis profiles showed that the microbial communities were significantly affected by the growth conditions and the presence of electrode, regardless of the circuit connection. Therefore, the electrode and circuit mode might help to control the amount of biomass and enhance the MFC performance.